Analisis Pengendalian Kualitas Produk Tiang Pancang di PT. X dengan Menggunakan Metode Failure Mode and Effect Analysis (FMEA) - Alda, Tania; Sukma Ompusunggu, Andika; Shalihin, Ahmad; Elsanna Revadi, Chindy; Ramadhani Putri Nasution, Fadylla; Atikah, Nurul; Purba, Naomi Cevania; Margaretta, Cinthya (LPPM-ITEBA, 2024)
This research was conducted at a company engaged in the precast concrete industry. The company produces and distributes piling products both domestically and abroad. The quality of pile products made by the company is one of the considerations of consumers. For this reason, the company must provide the best quality by utilizing all production factors as efficiently as possible. This is done to maintain consumer confidence and reduce the number of products that must meet company standards. This research aims to find the leading cause of defects in pile products. The method used is failure mode and effect analysis (FMEA). The FMEA method will look at the factors that cause defects based on the highest risk priority number (RPN). From the research results obtained, four factors cause defects in pile products, namely human factors, machine factors, material factors and method factors. Based on calculating the priority risk value in the FMEA method, the RPN value results are Machine Factors of 192, Material Factors of 180, Human Factors of 120, and Method Factors of 75. The factor causing the highest pile product defects is the machine factor, with an RPN value of 192. Based on this, it is known that the spinning machine used is too old and many machine components need to be replaced, so the proposed improvements given are to carry out regular and scheduled machine checks and maintenance and immediately repair or replace damaged machine components.